2014
DOI: 10.1097/jom.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Ambient Air Pollution and Serum Leptin in Older Adults

Abstract: Objective Long-term exposure to traffic-related air pollution has been linked to increased risk of obesity and diabetes and may be associated with higher serum levels of the adipokine leptin, but this hypothesis has not been previously evaluated in humans. Methods In a cohort of older adults, we estimated the association between serum leptin concentrations and two markers of long-term exposure to traffic pollution, adjusting for participant characteristics, temporal trends, socioeconomic factors, and medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 40 publications
1
34
1
Order By: Relevance
“…Strong and consistent evidence supports a link between oxidative stress, abnormal lipid, glucose and insulin metabolism and Alzheimer's disease (Nunomura et al, 2012;De la Monte, 2014;Castellani and Perry, 2014;Bonda et al, 2014aBonda et al, , 2014bButterfield et al, 2014;Wang et al, 2014aWang et al, , 2014b. In the setting of severe air pollution or in experimental models exposed to air pollution components (Levesque et al, 2011a(Levesque et al, , 2011b, the notion that AD is indicative of an active host response or environmental adaptation (Castellani and Perry, 2014), is biologically plausible and thus metabolic derangements involving inflammatory adipokines, insulin resistance and endothelial dysfunction in urban children are representing a vicious downward spiral involving the interactions between air pollutants, oxidative stress, genetics, and nutritional deficiencies.…”
Section: Discussionmentioning
confidence: 97%
“…Strong and consistent evidence supports a link between oxidative stress, abnormal lipid, glucose and insulin metabolism and Alzheimer's disease (Nunomura et al, 2012;De la Monte, 2014;Castellani and Perry, 2014;Bonda et al, 2014aBonda et al, , 2014bButterfield et al, 2014;Wang et al, 2014aWang et al, , 2014b. In the setting of severe air pollution or in experimental models exposed to air pollution components (Levesque et al, 2011a(Levesque et al, , 2011b, the notion that AD is indicative of an active host response or environmental adaptation (Castellani and Perry, 2014), is biologically plausible and thus metabolic derangements involving inflammatory adipokines, insulin resistance and endothelial dysfunction in urban children are representing a vicious downward spiral involving the interactions between air pollutants, oxidative stress, genetics, and nutritional deficiencies.…”
Section: Discussionmentioning
confidence: 97%
“…In a cross-sectional study of serum leptin levels in adults, there was a small association between black carbon exposure and serum leptin levels, but only when one of multiple modeling strategies was used. 15 …”
Section: Discussionmentioning
confidence: 99%
“…14 The effect decreased as children neared adolescence. A small cross-sectional study of adults in Boston 15 found an association between serum leptin levels, a correlate with body fat content, and black carbon levels.…”
Section: Introductionmentioning
confidence: 99%
“…34 Ambient levels of pollutants have been associated with BMI, 35 prevalent and incident diabetes, [36][37][38] and cardiometabolic measures such as insulin resistance and levels of serum leptin. 39 Whether individuals with existing diabetes 40 or metabolic syndrome 41 are more susceptible to the effects of air pollution than those unaffected by these conditions remains uncertain. 24,42 Effects of short-term exposure Short-term increases in urban air pollution are also associated with elevated mortality and morbidity ( Figure 4).…”
Section: The Effects Of Air Pollution On Cvdmentioning
confidence: 99%